Synthesis of ï§-Al2O3 Catalyst Support from Kaolin of Indonesian Origin - Samadhi, Tjokorde Walmiki; Subagjo, Subagjo; Lismana, Kevin R.; Fuadi, Khasin (ITB Journal Publisher, LPPM ITB, 2011)
KaolinÂ hasÂ beenÂ identifiedÂ asÂ aÂ potentialÂ rawÂ materialÂ forÂ the production ofÂ ï§-Al2O3Â forÂ hydrotreatingÂ catalyst support. This work explores the technicalÂ feasibilityÂ ofÂ applyingÂ theÂ potassiumÂ hydroxideÂ (KOH)Â e xtraction synthesis route on kaolinÂ from the BelitungÂ IslandÂ in Indonesia. The application ofÂ aÂ publishedÂ synthesisÂ methodÂ toÂ BelitungÂ kaolinÂ requiresÂ anÂ approximately twofoldÂ increaseÂ inÂ kaolinÂ calcinationÂ time,Â anÂ increaseÂ inÂ kaolinÂ calcination temperature from 950 to 1000 Â°C, and a tenfold increase in metakaolin extraction time, to obtain a specific surface area higher than 200 m2/g. The highest specific surface area of 233 m2/g was obtained whenÂ the kaolin was calcined at 1000 Â°C for 24 hours, and theÂ metakaolinÂ was extracted by concentrated KOHÂ solution for 12 hours.Â Phase characterization of the final product confirmed the formation of ï§-Al2O3, but with the inclusion of low-surface area ï¡-Al2O3 phase.